THE CHALLENGES AND DIFFICULTIES IN TEACHING WRITING: THE CHALLENGES AND DIFFICULTIES IN TEACHING WRITING - Mustofakulova, Maftuna (Журнал иностранных языков и лингвистики, 2022)
Abstract: As a teacher, I have faced a lot of challenges and difficulties in teaching writing in higher education system. With this regard, this article deals with the issues of how to solve those matters in class. The linguistic researches done in this sphere by some well-known scholars are also discussed and compared in terms of teaching writing for language learners and teachers. It should consider about some aspects in teaching writing